2023
DOI: 10.1039/d3cp00280b
|View full text |Cite|
|
Sign up to set email alerts
|

A redshifted photonic bandgap and wide-angle polarization selection in an all-hyperbolic-metamaterial one-dimensional photonic crystal

Abstract: According to the Bragg scattering theory, photonic bandgaps (PBGs) in all-dielectric one-dimensional (1-D) photonic crystals (PhCs) are polarization-insensitive. Such polarization-insensitive property of PBGs poses a challenge in wide-angle high-performance polarization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Nevertheless, owing to the strong optical absorption in HMMs, both the transmittance and polarization extinction ratio (PER) are not high. The maximum transmittance is only 50.8% and the maximum PER is only 3.82 × 10 1 [62].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, owing to the strong optical absorption in HMMs, both the transmittance and polarization extinction ratio (PER) are not high. The maximum transmittance is only 50.8% and the maximum PER is only 3.82 × 10 1 [62].…”
Section: Introductionmentioning
confidence: 91%
“…Under transverse electric (TE) polarization, the IFCs of HMMs are circles. Very recently, researchers selected two kinds of HMMs as the elements to constitute a class 1D photonic crystals (PCs) called all-HMM 1D PCs and then realized polarization-sensitive PBGs [62]. Under TM polarization, the PBGs in all-HMM 1D PCs shift towards longer wavelengths as the incident angle increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the incident angle results in a blue-shifted defect mode in the photonic band gap. On the other hand, the photonic band gap properties will be redshifted for TM polarization [36]. Thus, both conditions will aid in the detection of biomolecules.…”
Section: Design and Theorymentioning
confidence: 99%
“…Thus, both conditions will aid in the detection of biomolecules. Several studies have demonstrated that for greater incident angles, the sensitivity of biosensors is greater for TE polarization than for TM polarization [36][37][38]. Moreover, in 1D PhCs, TE polarized waves typically have a larger band gap than TM polarized waves [39,40].…”
Section: Design and Theorymentioning
confidence: 99%